2012
DOI: 10.3109/0167482x.2012.729111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an early intervention on perceived stress and diurnal cortisol in pregnant women with elevated stress, anxiety, and depressive symptomatology

Abstract: The goal of the present investigation was to examine effects of a cognitive-behavioral group intervention for pregnant women with subclinically elevated stress, anxiety and/or depression on perceived stress and salivary cortisol levels. Expectant mothers were recruited in gynaecologist practices. They participated in a screening, a standardized diagnostic interview (Munich-Composite Diagnostic Interview, M-CIDI), and were randomly assigned to an intervention (N = 21) and treatment as usual control group (N = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 38 publications
1
50
0
Order By: Relevance
“…cortisol awakening response) can be reduced during peripartum period by implementing relaxation techniques, psychoeducation, and cognitivebehavioural interventions (Bittner et al, 2014;Kozinszky et al, 2012;Richter et al, 2012;Teixeira et al, 2005;Urech et al, 2010;Urizar et al, 2004). These strategies may also have a positive impact on obstetric and neonatal outcomes (Fink et al, 2012).…”
Section: Resultsmentioning
confidence: 96%
“…cortisol awakening response) can be reduced during peripartum period by implementing relaxation techniques, psychoeducation, and cognitivebehavioural interventions (Bittner et al, 2014;Kozinszky et al, 2012;Richter et al, 2012;Teixeira et al, 2005;Urech et al, 2010;Urizar et al, 2004). These strategies may also have a positive impact on obstetric and neonatal outcomes (Fink et al, 2012).…”
Section: Resultsmentioning
confidence: 96%
“…Self-perceived stress is the cognitive appraisal of physical and environmental stressors and has been associated with increased levels of prenatal and postnatal serum cortisol. [38][39][40][41] Prolonged elevation of maternal serum cortisol levels can influence the infant immune system response and potentially the milk immune components (MICs). 42 Groer et al 42,43 reported higher self-perceived stress was associated with higher serum cortisol (r = 0.25, p = 0.040) as well as greater levels of milk secretory immunoglobulin A (SIgA).…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review identified 19 papers describing a total of 15 studies. Fifteen quantitative papers met inclusion criteria; two describe the same study with different outcome measures [ 35 , 36 ]. Four papers describing 3 qualitative studies were identified.…”
Section: Resultsmentioning
confidence: 99%
“…In one study cultural reasons may have accounted for the high attrition before the intervention started: women did not want to say no even if they had no intention of taking part [ 42 ]. There was speculation that women with symptoms which were just above the baseline threshold were not motivated enough to take part as they did not see the need for the course [ 23 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation